2019
DOI: 10.2147/ndt.s221908
|View full text |Cite
|
Sign up to set email alerts
|

<p>Experiences Of Immigrant Parents In Sweden Participating In A Community Assessment And Intervention Program For Preschool Children With Autism</p>

Abstract: BackgroundBarriers inherent in service systems for autism can hinder parents from getting help for their children, and this is probably especially true for immigrant parents. In order to provide accessible assessment and interventions for preschool children with autism, a multidisciplinary team was established in one district of a Swedish city, with a majority population of immigrants.AimThe aim of the present study was to gain knowledge of the parents' experiences of participating in the community assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 43 publications
0
36
0
Order By: Relevance
“…Vivanti et al ( 2018 , 2014 ) have emphasized the importance of understanding and taking into account the child’s characteristics as well as the family’s priorities/expectations, needs, and life situation in the selection of treatment objectives and treatment strategies. The importance of individually tailored interventions pursuant to the child’s needs as well as the parent’s resources and life situation, has been highlighted in a study by Nilses et al ( 2019 ) from our research group.…”
Section: Discussionmentioning
confidence: 88%
“…Vivanti et al ( 2018 , 2014 ) have emphasized the importance of understanding and taking into account the child’s characteristics as well as the family’s priorities/expectations, needs, and life situation in the selection of treatment objectives and treatment strategies. The importance of individually tailored interventions pursuant to the child’s needs as well as the parent’s resources and life situation, has been highlighted in a study by Nilses et al ( 2019 ) from our research group.…”
Section: Discussionmentioning
confidence: 88%
“…During the last decade, there has been an interest in looking at the unique diagnostic experiences of specific subgroups of parents and their children, including research focused on the experience of parents of girls with ASD (Rabbitte et al 2017), (Wiley et al 2014). Also, experiences of fathers of children with ASD (Hannon and Hannon 2017;Potter 2017), African American parents in the USA (Lovelace et al 2018;Pearson and Meadan 2018), Latino parents in the USA (Lopez et al 2018;Zuckerman et al 2014Zuckerman et al , 2017, immigrant families (Nilses et al 2019;Rivard et al 2019;Sakai et al 2019), and military families (Cramm et al 2019) have been studied.…”
Section: Specific Populationsmentioning
confidence: 99%
“…Immigrant families of children with ASD have reported that understanding the complex systems and medical terminology often resulted in delays in accessing the needed services for an evaluation (Habib et al, 2017; Jegatheesan et al, 2010; Khanlou et al, 2014; Wang & Casillas, 2013). Families found it unclear how services were connected or where they should start their journey for answers (Nilses et al, 2019; Rivard et al, 2019). This was often exacerbated by the distance between services and the lack of communication between various providers.…”
Section: Introductionmentioning
confidence: 99%